Genetic and epigenetic effects on couple adjustment in context of romantic relationship: A scoping systematic review - Khani, Pouria; Ansari Dezfouli, Mitra; Nasri, Farzad; Rahemi, Maryam; Ahmadloo, Salma; Afkhami, Hamed; Saeidi, Farzane; Tereshchenko, Sergey; Bigdeli, Mohammad Reza; Modarressi, Mohammad Hossein (Frontiers in Genetics, 2023)
Introduction: Couples’ relationships defined by a complex interaction between the two partners and their intrapersonal traits. Romantic; relationships and love are associated with marital satisfaction and stability, as well as couples’ happiness and health. Personality traits influence romantic relationships and, personality influenced by genetical and non-genetically factors. The roles of non-genetically factors such as socioeconomic position and external appearance have revealed in determining the quality of romantic relationships. Methods: We; performed a scoping systematic review to assess the association between genetics and epigenetic factors and romantic relationship. Relevant articles were identified by PubMed, EMBASE, Web of Science, Scopus, and the APA PsycInfo searching between inception and 4 June 2022. Results: Different studies evaluated the associated polymorphisms in 15 different genes or chromosomal regions. In the first step; we classified them into four groups: (1) Oxytocin-related signaling pathway (OXTR, CD38, and AVPR1A); (2) Serotonin-related signaling pathway (SLC6A4, HTR1A, and HTR2A); (3) Dopamine and catecholamine-related signaling pathway (DRD1, DRD2, DRD4, ANKK1, and COMT); and (4) other genes (HLA, GABRA2, OPRM1, and Y-DNA haplogroup D-M55). Then, we evaluated and extracted significant polymorphisms that affect couple adjustment and romantic relationships. Discussion: Overall, the findings suggest that genetic and epigenetics variants play a key role in marital adjustment and romantic relationships over time.